Development of a building energy analysis package (BEAP) and its application to the analysis of cool thermal energy storage systems - Senawi, M. Y. (2001)

(untitled)
This study develops a flexible, comprehensive and accurate microcomputer-based building energy analysis package. It involves the development of new programs and modifications of an existing simulation program. In the first part of the thesis, a simplified but accurate method of calculating thermal response factors for computing transient heat conduction through building envelope is presented. Efficient methods of calculating custom weighting factors for load estimation using the transfer function method are also developed. Exact models for the proportional control of variable air volume and mix box air dampers are developed for variable air volume and dual-duct/multi-zone systems, respectively. The modifications of an existing simulation program SHEAP, are described. In a validation study, strong agreement between simulation results from the new SHEAP-2 package, and the measured data of a test house is obtained. The new package is also verified using a commercial program. An efficient and accurate steady-state model of extended surface, air cooling and dehumidifying chilled-water coil is used to obtain a new and accurate off-design latent heat transfer performance correlation. Algorithms for efficient calculation of coil latent loads for constant air volume, dual-duct/multi-zone and variable air volume systems are presented. Accurate correlation for the off-design performance of forced draught, counter-flow and cross-flow air/water cooling towers is obtained from a cooling tower model, based on Merkel’s theory. The correlation is used in chiller algorithms for quick and accurate prediction of compressor energy consumption. Algorithms are developed for simulation of six generic cool thermal energy storage (CTES) systems. Their potential for capital and operating cost savings is investigated using simplified economic analyses. A library building is used as a simulation model to demonstrate the application of the new package for simulating CTES systems. The new package which is comprehensive and accurate (within 0.2 % of measured annual energy consumption), is useful for energy analysis in new and existing buildings, with or without CTES systems.